Maternal Dietary Protein Patterns During Pregnancy and the Risk of Infant Eczema: A Cohort Study - Zeng, Jingjing; Wu, Weijia; Tang, Nu; Chen, Yajun; Jing, Jin; Cai, Li (Frontiers in Nutrition, 2021)
Background: Previous studies have suggested that maternal dietary protein was associated with allergic diseases in offspring, but few studies have evaluated the influence of dietary protein patterns. This study aimed to explore the prospective association between maternal dietary protein patterns during pregnancy and the risk of infant eczema. Methods: A total of 713 mother-child pairs from a prospective cohort in Guangzhou, China were recruited. Maternal dietary protein was estimated using a validated face-to-face food frequency questionnaire. Dietary protein patterns were calculated based on the sources of protein. The data of infant eczema at 6 months was collected using the symptom questionnaire of eczema. Logistic regression was carried out to examine the associations between maternal dietary protein patterns and infant eczema. Results: The cumulative incidence of infant eczema at 6 months of age was 51.19%. Mothers of infants with eczema consumed more protein from poultry source during pregnancy than mothers of infants without eczema, while no statistical differences were observed in maternal intakes of protein from cereals and tubers, vegetables, fruits, red meat, fish and seafood, eggs, dairy, soybean, and nuts and seeds. Four dietary protein patterns were identified and termed poultry, plant, dairy and eggs, and red meat and fish. The cumulative incidence of eczema was 61.2%, 45.8%, 48.0%, 51.4% for these four patterns, respectively. Compared to the poultry dietary pattern, the plant pattern and the dairy and eggs pattern were associated with a reduced risk of infant eczema, and the adjusted odds ratios (95% confidence interval) were 0.572 (0.330-0.992), 0.478 (0.330-0.992), respectively. No such association was observed for the red meat and fish dietary protein pattern. Conclusion: This is the first study to investigate the association between maternal dietary protein during pregnancy and infant eczema from a whole-diet perspective. Compared with the poultry dietary protein pattern, the maternal plant pattern and the dairy and eggs pattern during pregnancy were associated with a reduced risk of infant eczema.